Zonificación de la capacidad portante del suelo del distrito de la banda de Shilcayo - Jiménez Flores, Jorge Fernando (2010)
All classification systems of primary interest for Geotechnical Engineer uses Atterberg limits (at least liquid and plastic) with a partial or full analysis of particle size, and the removal process for soil classification. In all classification systems it is absolutely essential to accompany the classification symbol for the proper description of the soil, for the particular symbol group is too broad and general as classification criteria for the specific soils. The Shilcayo river has enough influence on soil formation District Band Shilcayo because with the drag of stones comes from the dismemberment of elastic sedimentary rocks give the characteristics of stratigraphy to the riverbanks. Water on the floor, has a very important role in the mechanical properties of soils, for this reason it was very important to take into account the level of the water table. Performing the brink in each test pit made and adjacent places where it was feasible to obtain information by visual inspection. In the calculation or checking the bearing capacity of a land on which there is a building must be addressed in the short term (if undrained) and long term (with drainage). In the short-term behavior they despise all terms except the last cohesion, while the long-term carrying capacity (case drain) is also important in internal friction of the ground and its specific weight. The shear stress and pressure distribution, the basic principles are based to determine the values ​​of the angle of friction and cohesion soil (q> e) to then be applied formulas Terzaghi, Meyerhof, Hansen and Vesic after finishing Thus the permissible or tilling capacity.